Wikileaks dan Agenda Setting Media - Setyowati, Retno Manuhoro (Jurnal The Messenger, 2011)
Wikileaks frenetic appearance as a hacker organization state documents and other important information becomes a new phenomenon of life in the current global communication. Certainly, the phenomenon is also not missed the attention of the mass media worldwide, including in Indonesia. Through this case appeared a few thoughts about the position of a topic that could affect the media policy. Through agenda setting theory, obtained a description of the effects of issues on the media agenda, public agenda and policy agenda.